¡Cuidado animal! - Bosso, Andrés; San Juan, Gabriel; Gil, Guillermo; De Angelo, Carlos; Varela, Diego; Paviolo, Agustín (Revista Aves Argentinas, 2013)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).